Impact of agro-forestry systems on coffee yield, coffee plant morphology, physical and chemical attributes of green coffee beans and aroma generation of roasted coffee beans - XU, SU (2017)
A long experiment has been established since 2000 at CATIE (Tropical Agricultural Research and Higher Education Center), Turrialba, Costa Rica. Twenty agro-forestry systems with different shade types and managements (organic and non-organic) consisting of an incomplete randomized block-design with shade tree as main effect and subplots represented by management were set up. The mean 13-year yield, bienniality index (BI) of coffee yield, pruning, shade cover and morphology (height, diameter, total branches and productive branches) of coffee plants in these agro-forestry systems were measured. The effects of different managements and shade types on the physical and chemical attributes of green coffee beans and aroma and colour generation of roasted coffee beans were investigated. The organic management always showed the more stable production, while the coffee yield and morphology were always worse under the intensive organic (IO) management than under the intensive conventional (IC) management. Comparing with the moderate conventional (MC) management, the intensive organic (IO) management did not only have a similar or even higher productivity, but it also had higher total lipid and protein in the green beans and a stronger ability to generate more flavour and colour. The full sun system had a higher total coffee yield and bienniality index (BI) of coffee yield, green bean density and total protein content and greater flavour generation and colour after roasting. Comparing with the timber system, the service system did not only have the higher coffee yield and better coffee plant morphology, but it also produced green beans with higher total protein and roasted beans with the more flavour and colour. Comparing with the non-legume shade tree, the legume shade tree only influenced the total protein content of green coffee beans and further improved the performance of flavour and colour in the roasted coffee beans.